Information encoding methods based on ideal ring bundle - Talanchuk, Oleg; Riznyk, Oleg (Комп’ютерне моделювання та інформаційні технології, 2023)
Naturally, there is a need to protect information from unauthorized access, theft, destruction, distortion and other criminal acts. The concept of information vulnerability is introduced, which describes the effectiveness of selected methods for information protection. With the development and complication of methods and forms of automation of information processing processes, its vulnerability increases.The spectrum of problems expands significantly when the user starts working with wireless networks, because errors may occur during data transmission over these communication channels. Their reasons may be different, but the result is the same - the data is distorted and cannot be used on the receiving side for further processing.